2020
DOI: 10.1242/jcs.247783
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-directed microenvironment remodelling at a glance

Abstract: The tissue microenvironment supports normal tissue function and regulates the behaviour of parenchymal cells. Tumour cell behaviour, on the other hand, diverges significantly from that of their normal counterparts, rendering the microenvironment hostile to tumour cells. To overcome this problem, tumours can co-opt and remodel the microenvironment to facilitate their growth and spread. This involves modifying both the biochemistry and the biophysics of the normal microenvironment to produce a tumour microenviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 136 publications
0
18
0
Order By: Relevance
“…Prodrugs ideally release active parent drugs at targeted sites but remain intact in other cells and tissues [23]. Both oxidative reactive oxygen species (ROS) and reductive glutathione (GSH) are present in the TME [24]. Consequently, various tumor-specific stimuli responsive chemical bonds have been developed to produce smart antitumor prodrugs and nanomedicines [25,26].…”
Section: In Vitro Drug Releasementioning
confidence: 99%
“…Prodrugs ideally release active parent drugs at targeted sites but remain intact in other cells and tissues [23]. Both oxidative reactive oxygen species (ROS) and reductive glutathione (GSH) are present in the TME [24]. Consequently, various tumor-specific stimuli responsive chemical bonds have been developed to produce smart antitumor prodrugs and nanomedicines [25,26].…”
Section: In Vitro Drug Releasementioning
confidence: 99%
“…Subsequently, those samples were incubated at 37 °C and shaken at a speed of 100 rpm under dark conditions. Finally, cumulative amounts of DOX or MAG were detected at different time intervals (1,2,4,8,12, and 24 h) via UV spectrophotometers and the Agilent HPLC system at 480 and 290 nm, respectively. pH 7.4 PBS and a RPMI-1640 medium were utilized to evaluate the stability of MDHG NPs.…”
Section: Drug Release and Stability Of Mdhg Npsmentioning
confidence: 99%
“…2,3 HCC is not an isolated part; it closely interacts with the TME, which has not only tumor cells but also cancer-associated fibroblasts (CAFs), hepatic stellate cells, endothelial cells, and tumor-associated macrophages. 4 The CAFs are especially one of the major components in the TME and have numerous influences during tumor development. Previous reports demonstrated that activated CAFs by tumor cells secrete cell cytokines, including transforming growth factor-β1, platelet-derived growth factor, fibroblast growth factor, and stromal cell-derived factor 1, and then activated CAFs secretion of chemokine CCL2, CXCL8, and interleukin-6, which is beneficial to tumor cell proliferation, invasion, metastasis, epithelial-to-mesenchymal transition (EMT), tumor angiogenesis, and multidrug resistance.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tumor microenvironment plays a key role in promoting carcinogenesis and regulating cancer progression 1) . The interactions of tumor cells with their surrounding environment will ultimately determine their fundamental malignant characteristics and the behavior of tumors, such as metastatic potential and resistance against therapy.…”
Section: Introductionmentioning
confidence: 99%